Development and kinematic analysis of rocket launcher with different ball parameter / Muhammad Ilhan Salihin Alaman - Alaman, Muhammad Ilhan Salihin (2022)
This project involves designing, fabricating and calculations of a rocket launcher and which exhibits vertical projectile motion. For a rocket launcher to be made it first need to be designed and brainstormed for the ideas of the design first. The final design is then made into 3D by using the Solidwork software. After that, the design will be fabricated step by step by using the acquired material at the UiTM’s facilities and workshop. The finished product is then tested to test its performance and it is then used to achieve the objectives. As the title suggests, this project is used to determine the acceleration, velocity, and height of three different ball with different weight and size.